2023
DOI: 10.3389/fpsyt.2023.1123127
|View full text |Cite
|
Sign up to set email alerts
|

Role of uric acid as a biomarker of cognitive function in schizophrenia during maintenance period

Abstract: BackgroundPrevious studies involving uric acid (UA) in some specialized disease populations have found that high UA is associated with enhanced patient function. The mechanism to explain this association may be that UA, an important antioxidant, exerts neuroprotective effects. Patients with schizophrenia (SCZ) have severe oxidative stress abnormalities, and cognitive impairment is a major obstacle to their rehabilitation. Only few studies have been conducted on UA and cognitive impairment in SCZ. This study ai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 75 publications
0
1
0
Order By: Relevance
“… 67 , 68 There are no clear results on uric acid levels in patients with schizophrenia, but studies have shown a positive correlation between uric acid and cognitive function. 69 Even in the absence of a psychiatric diagnosis, elevated UA levels are associated with specific manic characteristics such as impulsivity, irritability, increased drive, and hyperthymia. 70 BD patients exhibit elevated central and peripheral pro-inflammatory factors (cytokines, chemokines, acute phase reactants, oxidation/nitride substances), increased expression of inflammatory genes, and abnormal activation of cells (t cells, monocytes, microglia) and complement.…”
Section: Discussionmentioning
confidence: 99%
“… 67 , 68 There are no clear results on uric acid levels in patients with schizophrenia, but studies have shown a positive correlation between uric acid and cognitive function. 69 Even in the absence of a psychiatric diagnosis, elevated UA levels are associated with specific manic characteristics such as impulsivity, irritability, increased drive, and hyperthymia. 70 BD patients exhibit elevated central and peripheral pro-inflammatory factors (cytokines, chemokines, acute phase reactants, oxidation/nitride substances), increased expression of inflammatory genes, and abnormal activation of cells (t cells, monocytes, microglia) and complement.…”
Section: Discussionmentioning
confidence: 99%